Strategi dalam Meningkatkan Kualitas Pelayanan RSI Ibnu Sina Yarsi Padang Panjang - Lidra Firdaus; Diga Putri Oktaviane; Wahib Ashari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Ibnu Sina Yarsi Islamic Hospital Padang Panjang plays a crucial role in providing medical services to the community. However, challenges such as inadequate facilities, limited service space, and insufficient healthcare personnel have led to long queue times and schedule mismatches, adversely affecting patient satisfaction. This study analyzes strategies to improve service quality at the hospital using a qualitative descriptive approach with data collected through observation, interviews, and documentation involving management, medical staff, and patients. Data validity was ensured by triangulation, and analysis followed the Miles and Huberman interactive model. The findings reveal that strategies focusing on human resource development programs, performance-based budget management, and consistent application of standard operating procedures (SOP) have been implemented effectively. Despite this, limitations in human resources, budget, and physical infrastructure hinder optimal results. Strengthening internal capacity and resource optimization are necessary to achieve sustainable improvements in service quality.